Strategi Optimalisasi Jimpitan sebagai Upaya Membangun Ketahanan Sosial Warga RT 01 RW 01 KedungSolo, Porong, Sidoarjo - Siti Fatimah; Nadiyah Anggun Eka Wardani; Nafi' Mardiansyah; Dhimas Ali Shibri; Taqwanur (Jurnal Pengabdian Masyarakat Indonesia (JPMI), 2025)
Jimpitan is a form of local wisdom that continues to exist and develop in RT 01 RW 01 KedungSolo, Porong, Sidoarjo, as a community-based mechanism for managing collective funds. This community service activity aims to optimize jimpitan in strengthening social resilience through student assistance in collaboration with the neighborhood leaders and residents. The program was carried out in August 2024 using a participatory approach through observation, discussions, and direct involvement in collecting and recording contributions. The results show diversification of income sources from routine contributions and additional fees, innovation in exchanging small change with local microenterprises that support the local economy, and the use of funds for public facilities and socio-religious activities. Students played an active role in recording, recap, financial report analysis, and promoting transparency, making the jimpitan practice more organized, accountable, and replicable in other communities with adjustments to local conditions.